A benefit and the prospects of IL-6 inhibitors in idiopathic multicentric Castleman's disease. Issue 2 (4th March 2019) - Koga, Tomohiro; Sumiyoshi, Remi; Kawakami, Atsushi; Yoshizaki, Kazuyuki
Abstract: Castleman's disease (CD), a heterogeneous group of lymphoproliferative disorders, is divided into unicentric CD (UCD) and multicentric CD (MCD) based on the number of regions of enlarged lymph nodes with characteristic histopathologic features. The clinical pictures and treatment differ greatly between these UCD and MCD. In MCD, cases of human herpesvirus 8-negative patients with unknown etiology are defined as idiopathic MCD (iMCD). Most cases of UCD are treatable by surgical excision. The prognosis of iMCD varies, and it may be challenging to achieve remission. Glucocorticoids are initiated as the first choice for therapy, but for glucocorticoid-resistant cases, interleukin (IL)-6 inhibition is initiated. However, an IL-6 inhibitor is not effective for all iMCD cases, and refractory cases occur despite these treatments. In this review, we briefly summarize the role of IL-6 in iMCD, and we discuss the efficacy that has been reported for tocilizumab (TCZ), the anti-IL-6 receptor antibody, for patients with iMCD in Japan. Factors predicting the therapeutic response to IL-6 remain to be identified, and the verification of the long-term safety of IL-6 inhibition is needed.